Alleviation of cadmium accumulation in maize (Zea mays L.) by foliar spray of zinc oxide nanoparticles and biochar to contaminated soil. (May 2019) - Rizwan, Muhammad; Ali, Shafaqat; Zia ur Rehman, Muhammad; Adrees, Muhammad; Arshad, Muhammad; Qayyum, Muhammad Farooq; Ali, Liaqat; Hussain, Afzal; Chatha, Shahzad Ali Shahid; Imran, Muhammad
Abstract: Due to the increase in area of cadmium (Cd)-contaminated soils worldwide, effective measures are necessary to minimize the Cd accumulation in cereals including maize ( Zea mays L.) plant. A study was therefore performed to explore the effectiveness of foliar spray of zinc oxide (ZnO) nanoparticle (NPs) alone (0, 50, 75, 100 mg/L) or combined with soil application of biochar (1.0% w/w) on biomass, antioxidant enzyme activity and Cd concentrations in maize plants grown on a Cd-contaminated soil. The results depicted that ZnO NPs alone or in combination with biochar improved the height of maize plants, number of leaves, shoot and roots dry biomass, chlorophyll concentrations and gas exchange attributes. All the amendments reduced the electrolyte leakage, malondialdehyde, and hydrogen peroxide contents while improved the activities of antioxidant enzymes in leaf and roots of maize over the control. The application of 50, 75 and 100 mg/L ZnO NPs reduced the Cd contents in shoots by about 12%, 23, and 61%, and in roots by 18%, 33%, and 53%, respectively, over the control. The Cd concentrations in shoot decreased by 15%, 28%, and 68% and in roots by 14%, 35, and 55% after biochar combined with foliar spray of 50, 75 and 100 mg/L ZnO NPs, respectively. All the amendments improved the Zn concentrations in maize shoots and roots whereas reduced the soil bioavailable Cd. Overall, biochar combined with foliar spray of ZnO NPs could be recommended for safely growing the crops on Cd-contaminated soils. Graphical abstract: Image 1 Highlights: Biochar and zinc nanoparticle (ZnO NPs) increased the maize biomass. Biochar and ZnO NPs reduced the Cd and increased the Zn concentrations in maize. Biochar and ZnO NPs reduced the oxidative stress and increased the enzyme activities. There was significant effect of biochar × ZnO NPs on Cd concentration in maize. Abstract : Combined application of NPs and biochar is effective in reducing Cd concentration in maize plants.